Integration of Black Phosphorus Photoconductors with Lithium Niobate on Insulator Photonics. Issue 2 (20th November 2022) - Wang, Shifan; Chapman, Robert James; Johnson, Brett C.; Krasnokutska, Inna; Tambasco, Jean‐Luc J.; Messalea, Kibret; Peruzzo, Alberto; Bullock, James
Abstract: Photodetectors formed with layered two‐dimensional (2D) materials have shown significant potential for integration with photonic circuits, offering fast, high responsivity and low noise detection over a broad range of optical wavelengths. However, only preliminary trials of this concept have been performed on emerging photonics platforms such as lithium niobate on insulator (LNOI). In this study, a novel architecture consisting of ≈15 nm thick layered black phosphorus (bP) photoconductors draped over LNOI waveguides is demonstrated. The performance of these detectors is studied across the telecom bands at room temperature, and a high extrinsic responsivity of 148 mA W −1 is measured at λ = 1550 nm under low bias conditions ( V DS  = 0.3 V). The spectral response of the detectors is broad allowing the response of other photonic components, such as fiber‐to‐chip grating couplers, to be characterized in situ, without need to out‐couple the light. Finally, the speed of the bP detectors is found to be beyond our instrumentation, setting 100 ns as an upper‐limit rise/fall time, with the actual speed of the bP detector likely to be much faster. Abstract : For the first time the integration of the van der Waals material black phosphorus with lithium niobate on insulator waveguides is demonstrated, to form telecom band photoconductors. These detectors exhibit a high extrinsic responsivity of 148 mA W −1 measured at λ = 1550 nm under low bias conditions ( V DS  = 0.3 V) with the potential for high‐speed operation.